Moneys Financial Record Application Design for Mobile-Based Students - Dwiwahyu, Anisah Nurdina; Wardani, Indri Eka; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Students who are in the transition period from youth to adulthood still do not have a stable emotional level that can manage and handle money. It takes careful preparation to handle funds so that the money earned can be used according to its purpose. We now live in the mobile era, therefore we need a mobile application. The design of this application begins with the identification of information needs and the presence of attractive and complete features in the application that make students interested in using it. The research findings show that students want a live app with features to track their expenses, income, and budget. Using Android as a foundation, the Moneysv app can be created. The mobile-based Moneysv Financial Management application uses the Java programming language, Notepad++ application software, and Android SDK, which types the program code and application logic. SQLite is used to create the database structure. With the Black Box testing approach, system testing procedures can be performed. "Black Box testing technique is a kind of testing that deals with software whose internal performance is unknown. In this research, an application by the name of Moneysv is a financial record application, among others, a student financial planning tool that can make it easier for students to develop financial plans by allowing them to record budgets, income, expenses, and management in an easy way. This is one of the findings of the research conducted.